2020
DOI: 10.3389/fcell.2020.00434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Cardiomyocyte Death in Drug-Induced Cardiotoxicity

Abstract: Homeostatic regulation of cardiomyocytes plays a crucial role in maintaining the normal physiological activity of cardiac tissue. Severe cardiotoxicity results in cardiac diseases including but not limited to arrhythmia, myocardial infarction and myocardial hypertrophy. Drug-induced cardiotoxicity limits or forbids further use of the implicated drugs. Such drugs that are currently available in the clinic include anti-tumor drugs (doxorubicin, cisplatin, trastuzumab, etc.), antidiabetic drugs (rosiglitazone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 190 publications
(194 reference statements)
1
68
0
1
Order By: Relevance
“…Pyroptosis was first demonstrated in 2001 60 and is now widely recognized to play a crucial role in the pathogenesis of cardiovascular diseases 61 . Pyroptosis is characterized by increased inflammation and activation of caspase -1, caspase-3, caspase-4, and caspase-11 as well as NLR family pyrin domain containing 3 (NLRP3) leading to the cleavage of Gasdermin D (GSDMD) or GSDME and to the rupture of the plasma membrane that allows the release of interleukin-1beta (IL-1β) and IL-18 62 64 .…”
Section: Pyroptosismentioning
confidence: 99%
“…Pyroptosis was first demonstrated in 2001 60 and is now widely recognized to play a crucial role in the pathogenesis of cardiovascular diseases 61 . Pyroptosis is characterized by increased inflammation and activation of caspase -1, caspase-3, caspase-4, and caspase-11 as well as NLR family pyrin domain containing 3 (NLRP3) leading to the cleavage of Gasdermin D (GSDMD) or GSDME and to the rupture of the plasma membrane that allows the release of interleukin-1beta (IL-1β) and IL-18 62 64 .…”
Section: Pyroptosismentioning
confidence: 99%
“…Doxorubicin may induce cardiotoxicity through inhibition of topoisomerase II, oxidative stress, dysregulation of intracellular calcium signaling, mitochondrial impairment, and apoptosis ( 5 , 6 ). Our lab has recently shown that death receptor signaling driven by p53 is an additional critical component of doxorubicin-induced cardiotoxicity ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Protection against cancer treatment-induced cardiotoxicity is challenging, because shared mechanistic pathways may contribute to both the tumor suppressive and the cardiotoxic effects of cancer treatments. For instance, anthracycline-induced apoptotic cell death is a shared pathway for the anti-cancer and cardiotoxic effects of anthracyclines [ 6 ]. Cardioprotective agents that have non-selective anti-apoptotic effects will likely inhibit the anti-cancer effects of anthracyclines.…”
Section: Introductionmentioning
confidence: 99%